Inequality and quiescence: a continuing conundrum - Ray Pahl; David Rose; Liz Spencer (University of Essex, Institute for Social and Economic Research (ISER), 2007)
How may we account for the fact that most people appear to accept widespread social and economic inequalities? This is a question that has often been posed in the social sciences. One possible explanation is that individuals tend to make comparisons with others like themselves and so, as a result, do not appreciate the full range of inequality. This was the conclusion drawn by research in the 1960s and was re-affirmed by further research in the 1970s. However, more recently, it has been suggested that social and economic change in the intervening period may have had effects on the range and type of comparisons people are able to make. In particular, it has been argued that the growth of the mass media has exposed people to a broader range of lifestyles and the expansion of the consumer society has created ever greater desires. In these circumstances, it is thought that peoples horizons will have expanded so that they no longer have such restricted points of reference for their social comparisons. In this paper, we use evidence from a small scale pilot qualitative study to investigate social comparisons in the 21st century. We find that, in many ways, social comparisons are still narrow and knowledge of the true extent of inequality is still limited. What comparisons people do make appear to be based on lifestyle and consumption. Hence, they are neither resentful of the superrich, nor of others closer to themselves who have done better in life. However, they are very aware of their advantages compared with less fortunate members of society. Our respondents see themselves as members of a comfortable middle mass of ordinary, hard-working families. The paper concludes with some reflections on the nature of social cohesion in the UK today.
Keywords: 330